Mining Law in Cameroon: A Blueprint for Investors in the Sector - Enow Godwill Baiye (Studies in Law and Justice, 2024)
Cameroon is currently at an important crossroads as far as the development of the mining sector is concerned. In recent times, the mining sector has undergone series of legislative reforms with the aim to spur the interest of investors in this sector of the economy. These legislative reforms have also been in line with the country’s vision to become emergent by 2035, with the mining sector been one of those sectors to spur the realization of this vision. This paper therefore aims at examining the extent to which the Cameroonian mining law has become a tool to attract investors in this sector of the economy which in the past decades has witnessed a downturn of investors. The paper makes use of the qualitative research methods. Despite significant strides that the Cameroonian government has made to make to lure the interest of investors, inadequacies of the mining law, lack of transparency and accountability, discrimination in terms of obtaining certain mining licences and political instability are the major setbacks that has hindered the continuous growth of the sector. It is in this light that the research recommends both nationals and non-nationals should be involved in artisanal mining, tax and customs incentives should not only be limited to holders of semi mechanized and industrial mining permits or licences, transparency and accountability should be strengthened through continuous publication of mining data and declaration of revenue obtained from this sector, and rehabilitation of the mining sites should be effectively supervised by the concerned body.